Analisis Kinerja Produksi Sumur LX Menggunakan Artificial Lift PCP dan SRP Serta Pendekatan Keekonomian - Gunawan, Benny; Eklezia Dwi Saputri, Eriska; Triono, Agus (Petroleum Engineering, Faculty of Engineering, University of Jember, 2025)
In the oil industry, the main challenge is to maintain a stable oil production rate, especially when reservoir pressure decreases. Therefore, artificial lift methods are used to increase production rates. The LX well is one of the wells located in the Tarakan field, North Kalimantan, where at the beginning of production the Artificial Lift method had not been used. This study aims to analyze the production performance and economic aspects of the use of 2 artificial lift methods, namely Progressive Cavity Pump (PCP) and Sucker Rod Pump (SRP). The simulation results show that the flow rate increases with increasing operating speed and number of strokes per minute. The optimal speed for PCP is 400 rpm with a flow rate of 1668.14 STB/d, while for SRP, the optimal SPM is 22 with a flow rate of 1686.89 STB/d. The analysis of the economic calculation of the use of the PCP artificial lift method obtained a POT of 0.69 years. Calculation with DCA method, obtained IRR ranging from 132% - 133% and NPV ranging from 3,499,432 - 3,842,340. Based on the results of economic calculations from the use of the SRP artificial lifting method, the POT is 1 year. Calculation with the DCA method obtained IRR values ranging from 82% - 84% and NPV ranging from 1,661,827 - 2,008,573. These results indicate that this project is financially feasible.